2023
DOI: 10.1002/syst.202200036
|View full text |Cite
|
Sign up to set email alerts
|

Transient Biomacromolecular Nanoparticles for Labels with Self‐Erasable and Rewritable Ability

Abstract: Nature utilizes non-equilibrium self-assembly to achieve remarkable functions. Although such systems have been synthesized, this class of assembly is only sparsely explored in innovative materials with life-like functions. Here, we report transient nanoparticles driven by adenosine triphosphate and their applications on the self-erasable and rewritable security labels. We show that the lifetime of transient nanoparticles can be tuned from a few minutes to hundreds of minutes through adjusting concentrations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…The authors demonstrate the application of this DSA system in encryption and self‐erasing inks based on its fluorescence variation behavior. Li and coauthors have also reported an ATP‐fueled DSA system [86] . In this work, they presented outstanding self‐erasable and rewritable labels using a DSA system with space and time dimensions encoding information encryption.…”
Section: Applications Of Dissipative Self‐assemblymentioning
confidence: 91%
See 1 more Smart Citation
“…The authors demonstrate the application of this DSA system in encryption and self‐erasing inks based on its fluorescence variation behavior. Li and coauthors have also reported an ATP‐fueled DSA system [86] . In this work, they presented outstanding self‐erasable and rewritable labels using a DSA system with space and time dimensions encoding information encryption.…”
Section: Applications Of Dissipative Self‐assemblymentioning
confidence: 91%
“…Li and coauthors have also reported an ATP-fueled DSA system. [86] In this work, they presented outstanding self-erasable and rewritable labels using a DSA system with space and time dimensions encoding information encryption. Thus, the DSA system platform is one of the best models for creating self-erasing and encrypting inks as a result of the time-dependent dynamics and reversible characteristics.…”
Section: Self-erasable Inksmentioning
confidence: 99%
“…The group of van Eelkema and van Esch pioneered the development of out-of-equilibrium supramolecular hydrogels using methylation reagents as the fuels. 22,53 After that, various beautiful examples of out-of-equilibrium supramolecular assemblies powered by different chemical fuels, including carbodiimide, [57][58][59][60][61][62] ATP, 55,[63][64][65][66][67][68][69] pH regulators, [70][71][72][73][74][75] enzymatic reactions, 15,66,[76][77][78] carbon dioxide, 79,80 and others, [81][82][83][84] have been carefully developed. The resultant supramolecular hydrogels show high dynamics, tunable lifetime and stiffness, and a regenerative capability.…”
Section: Shengyu Baimentioning
confidence: 99%